The skull, jaw muscles and cranial kinesis of Dibamus novae-guineae with special reference to the systematic position on the Dibamidae - De Weerdt, Abraham Francois (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 1971.